Hematological Profile in Dairy Cattle with Foot and Mouth Diseases in Lembang, West Bandung - Majid, Rully Abiyoga; Septiyani, Septiyani; Gradia, Resti; Rosdianto, Aziiz Mardanarian; Hidayatik, Nanik (Universitas Airlangga, 2023)
Foot and mouth disease (FMD) is a widespread infectious disease that significantly affects the dairy farming sector in Indonesia. In reducing the impact caused by FMD, proper treatment performed by veterinarians is necessary. Hematological profile can be used as a data reference to prioritize dairy cattle infected with FMD. This study aimed to describe the hematological profile in dairy cattle with FMD infection. This study was collected data from 15 dairy cattle with FMD infection at Koperasi Peternak Sapi Bandung Utara (KPSBU), Lembang, West Bandung, West Java, Indonesia. Parameters observed in the hematology analyzer were the numbers of erythrocytes, leukocytes, lymphocytes, neutrophils, platelets, hemoglobin, hematocrit, MCV, MCH, MCHC, RDW, and MPV. The results of the examination of hematological profile showed various numbers. It found lymphopenia, neutrophilia, and high MPV values. It was suggested for veterinarians to refer to this study's results to determine an effective and efficient treatment.